Microbial Induction of Immunity, Inflammation, and Cancer - O'Keefe, Stephen J.; Greer, Julia B. (Frontiers in Physiology, 2011)
The human microbiota presents a highly active metabolic that influences the state of health of our gastrointestinal tracts as well as our susceptibility to disease. Although much of our initial microbiota is adopted from our mothers, its final composition and diversity is determined by environmental factors. Westernization has significantly altered our microbial function. Extensive experimental and clinical evidence indicates that the westernized diet, rich in animal products and low in complex carbohydrates, plus the overuse of antibiotics and underuse of breastfeeding, leads to a heightened inflammatory potential of the microbiota. Chronic inflammation leads to the expression of certain diseases in genetically predisposed individuals. Antibiotics and a ‘clean’ environment, termed the ‘hygiene hypothesis’, has been linked to the rise in allergy and inflammatory bowel disease, due to impaired beneficial bacterial exposure and education of the gut immune system, which comprises the largest immune organ within the body. The elevated risk of colon cancer is associated with the suppression of microbial fermentation and butyrate production, as butyrate provides fuel for the mucosa and is anti-inflammatory and anti-proliferative. This article will summarize the work to date highlighting the complicated and dynamic relationship between the gut microbiota and immunity, inflammation and carcinogenesis.